2017
DOI: 10.12688/wellcomeopenres.13119.1
|View full text |Cite
|
Sign up to set email alerts
|

Using mitoribosomal profiling to investigate human mitochondrial translation

Abstract: Background: Gene expression in human mitochondria has various idiosyncratic features. One of these was recently revealed as the unprecedented recruitment of a mitochondrially-encoded tRNA as a structural component of the large mitoribosomal subunit. In porcine particles this is mt-tRNA Phe whilst in humans it is mt-tRNA Val. We have previously shown that when a mutation in mt-tRNA Val causes very low steady state levels, there is preferential recruitment of mt-tRNA Phe. We have investigated whether this altere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…For mRNAs with a concise (1–3 nt) leader or no (0-nt) leader, the plots reveal an enrichment of 15-nt half-size RPFs increasing in size to full-length, at which point the mRNA channel is fully occupied. These shorter half-footprints have not been previously detected ( 30 ) and indicate that mitoribosomes load at the ends of messages with the P site on the start codon. Translation initiation occurs from the canonical AUG but also AUA and AUU.…”
Section: Resultsmentioning
confidence: 52%
“…For mRNAs with a concise (1–3 nt) leader or no (0-nt) leader, the plots reveal an enrichment of 15-nt half-size RPFs increasing in size to full-length, at which point the mRNA channel is fully occupied. These shorter half-footprints have not been previously detected ( 30 ) and indicate that mitoribosomes load at the ends of messages with the P site on the start codon. Translation initiation occurs from the canonical AUG but also AUA and AUU.…”
Section: Resultsmentioning
confidence: 52%
“…The sucrose density gradient with ultracentrifugation has been applied to enrich mitoribosomes and their footprints and deplete cytosolic ribosome (cytoribosome) footprints in order to survey mitochondrial translation by Ribo-Seq 8, [10][11][12][13][14][15][16] . A drawback of this strategy is in its limitation in handling many samples (i.e., the maximum number of samples is limited to the 6 tubes that the ultracentrifuge rotor holds) as well as its timeconsuming nature (~1 d).…”
Section: Development Of Mitoip-thor-ribo-seqmentioning
confidence: 99%
“…A variety of techniques have been developed to investigate translation in mitochondria 8 . Among them, mitochondria-optimized ribosome profiling (or Ribo-Seq), which is based on deep sequencing of ribosome-protected RNA fragments remaining after RNase digestion 9 , has been a powerful tool (MitoRibo-Seq) [10][11][12][13][14][15][16] . Technically, MitoRibo-Seq requires the depletion of cytosolic ribosome (cytoribosome) footprints; otherwise, they occupy large sequencing space.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, experiments in Drosophila suggested that, in some cases, tRNA synthetase undergoes coordinated changes alongside their corresponding tRNAs to maintain function (Meiklejohn et al, 2013;Holmbeck et al, 2015). The availability of ribosome profiling as a highly quantitative approach to assess rates of translation, and its recent adaptation to the mtDNA (Rooijers et al, 2013;Gao et al, 2017), serves as a promising future experimental approach to compare rates of mtDNA translation between samples differing in synonymous mtDNA mutations.…”
Section: Identifying the Signatures Of Selection-assessing The Functimentioning
confidence: 99%